Islamic Legal Discourse and Gender Inclusivity: The Dynamics of Khunthā/Hijra and Transgender Identity in Bangladesh - Hasan, Md. Mahdi; Mutaqin, Zezen Zaenal (Fakultas Syariah UINSI Samarinda, 2025)
This paper critically explores the theological, legal, and sociopolitical distinction between traditional khunthā (intersex) and contemporary socially constructed transgender identities within the framework of Islamic jurisprudence, focusing on the Bangladeshi context. By engaging with classical and contemporary Islamic legal texts, religious interpretations, legal precedents, scholarly works, media representations, and public discourse, the study argues that the conflation of khunthā (often culturally aligned with hijra) and transgender identities in public narratives—particularly in education and media—has led to widespread confusion, societal backlash, and policy resistance. While khunthā has traditionally been recognized in Islam as part of divine creation (aṣl al-khilqah), transgender identity—defined as a divergence from one’s biological sex—is often perceived as altering God’s creation (taghyīr al-khilqah) and thus faces greater religious and social resistance. This paper also addresses concern about unverified gender identity claims, citing incidents where individuals falsely claimed gender status, resulting in misuse of institutional provisions and violations of women’s safety and privacy in gender-segregated spaces. The study suggests that future policy initiatives on gender inclusivity in Muslim-majority countries like Bangladesh should clearly distinguish between traditional legitimate gender and socially constructed gender identities in order to uphold religious and ethical values and prevent misuse in gender-segregated spaces.